2019
DOI: 10.1080/02508060.2019.1615773
|View full text |Cite
|
Sign up to set email alerts
|

An ecological perspective on a river’s rights: a recipe for more effective water quality governance?

Abstract: In several countries, the transfer of legal rights to rivers is being discussed as an approach for more effective water resources management. But what could this transfer mean in terms of a healthy river? We address this question by identifying the ecological requirements for naturally functioning rivers and then explore the demands which these requirements impose on society, the current policy responses to these requirements and whether the transfer of rights to the river could facilitate the preservation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Procedural right questions such as the right of information, the right to participate and the right of access to justice, or substantive right questions such as a rivers' right to be protected from pollution to maintain its good ecological status. For more details, see Wuijts et al (2019).…”
Section: Resultsmentioning
confidence: 99%
“…Procedural right questions such as the right of information, the right to participate and the right of access to justice, or substantive right questions such as a rivers' right to be protected from pollution to maintain its good ecological status. For more details, see Wuijts et al (2019).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the results from a systematic literature review [32] and case study material from The Netherlands [33][34][35] are combined in a joint analysis of governance conditions needed for water quality improvement. Due to the procedural nature of the WFD, its mode of implementation into national law and policy programs varies between countries and this may influence its results.…”
Section: Methodsmentioning
confidence: 99%
“…The review also showed that perspectives between scholars from social-economic, legal and ecological knowledge domains can be different and that these differences and the interactions between these knowledge domains should be accounted for in a governance approach. This observation is used to analyze the results of the empirical studies [33][34][35] to identify governance conditions additional to the governance conditions that were identified using the analytical framework (see Section 2.2.3).…”
Section: Materials 221 Input From Literature Reviewmentioning
confidence: 99%
“…The current subdivision in the WFD between hydro-morphological elements supporting biological elements (variation in depth, substrate, structure of the riverbank or tidal zone, flow quantity and dynamics, and river continuity) and chemical elements (salinity, dissolved substances including turbidity) ignores some of the most crucial systemic characteristics of riverine and estuarine systems, namely the interplay between the different aspects of hydromorphodynamics. Although it would thus result in an incomplete approach to restoring a natural water system, this subdivision is nevertheless employed in other places where focus lies on an ecological perspective, such as Wuijts et al (2019). Salinity in particular is currently considered a characteristic of the chemical state, or indicative of the types of flora and fauna that can reside in such waters.…”
Section: Static Regulation In a Dynamic Natural Systemmentioning
confidence: 99%